The Condition Of Mandarin Language Learning In Indonesia - Shenglin, Zhang; Ying, Yi (Bina Nusantara University, 2012)
The condition of Mandarin language learning in Indonesia was still a main issue for Mandarin lecturers and researchers in China and Indonesia. To find out the clear condition, a research having a combination of qualitative and quantitative methods was done, in which questionairs were distributed and interviews with Mandarin students, lecturers, and experts were conducted. Respondents were selected by random sampling. After data analysis, a conclusion which indicates a general condition and some problems in the process of teaching and learning Mandarin, as well as the use of learning materials can be presented. The research results show that at present, the Mandarin learners are still dominated by the descendants of Tionghoa, even though learners coming from non-Tionghoa’s descendants are getting increase; learners’ motivation in studying Mandarin is closely related with the self-identity as Tionghoa’s descendants and the job’s demands; Mandarin language still belongs to the second language in Indonesia and has not able to replace the domination of English; the insufficiency of lecturers and learning materials in the past have significantly provided, but this condition has not solved the problems, especially which concerns to the improvement of the quality of learners and local learning materials.